Choroba Fabry'ego u członków jednej rodziny - trudności diagnostyczne związane z polimorfizmem genowym - Bielak, Joanna; Czyżyk, Elżbieta; Ługowska, Agnieszka; Tylki-Szymańska, Anna (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Fabry disease is a rare lysosomal disease, inherited in the X-linked manner. It is caused by a mutation in the gene GLA locus Xq22 which results in a deficiency of the enzyme-galactosidase and deposition of globotriaosylceramide (GL3) in the tissues and organs of patients. Its prevalence is estimated at 1:40 000-1:120 000 live male births. The women who carry the mutation rarely remain asymptomatic. The majority of symptoms characteristic of Fabry disease occur with varying intensity, but lesser than in case of male hemizygotes. The exception is when there is an unfavorable model of a random inactiva¬tion of one of two X chromosomes. In this case, a female can present the symptoms as severe as the man with the full-blown Fabry disease. The characteristic symptoms of Fabry disease are: pain in the extremities and in the abdomen which appears in a childhood, and later, the skin lesions (angiokeratoma), a lack of sweating, diarrhea, cardiomyopathy and the kidneys damage leading to their renal failure. There are also changes in the vision organ. The authors present a case of the family of four where all members were found with a decreased activity of alpha-galactosidase in the dry blood spot and leukocytes, and two different mutations in the GLA gene.